Clinical validation of urine-based Xpert® MTB/RIF assay for the diagnosis of urogenital tuberculosis: A systematic review and meta-analysis. (June 2020) - Chen, Ke; Malik, Aijaz Ahmed; Nantasenamat, Chanin; Ahmed, Sarfraz; Chaudhary, Omkar; Sun, Changfeng; Sheng, Yun-Juan; Chen, Wen; Gang, Wu; Deng, Cun-Liang; Ojha, Suvash Chandra
Highlights: Low accuracy of conventional testing complicates clinical management of urogenital tuberculosis. Xpert demonstrates promising diagnostic efficiency for urogenital tuberculosis. Xpert performance may not be affected by differing characteristics of included studies. Integrating traditional tests with Xpert assay may increase likelihood of urogenital tuberculosis detection. Abstract: Objectives: Effective methods for diagnosing urogenital tuberculosis (UGTB) are important for its clinical management. Therefore, we undertook a systematic review to assess the performance of the urine-based Xpert MTB/RIF assay for UGTB. Methods: PubMed, Embase, Web of Science, the Cochrane library, and Scopus were systematically searched up to July 30, 2019. A hierarchical summary receiver operating characteristic (HSROC) was applied to calculate the pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), and odds ratio (OR) for the diagnostic accuracy of the Xpert test. Results: Our search identified 858 unique articles from which 69 studies were selected for full-text revision, with 12 studies meeting the inclusion criteria. Eleven studies comprising 1202 samples compared Xpert with mycobacterial culture, while 924 samples from eight studies compared it with a composite reference standard (CRS). The values for pooled sensitivity, specificity, PLR, NLR, and OR were 0.89, 0.95, 20.1, 0.18, and 159.53, respectively, when compared with the mycobacterial culture. Likewise, when compared with a CRS, the respective pooled sensitivity, specificity, PLR, NLR, and OR values were 0.55, 0.99, 40.67, 0.43, and 166.17, thereby suggesting a high level of accuracy for diagnosing UGTB. A meta-regression and sub-group analysis of TB-burden countries, study design, decontamination, concentration, and reference standard could not explain the heterogeneity ( p > 0.05) in the diagnostic efficiency. Conclusions: Our results suggested that Xpert is a promising diagnostic tool for the diagnosis of UGTB via urine specimen.